Al-Wujuh Wa Al-Nazhair Dalam Alquran Perspektif Historis - Wahyudi Wahyudi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
This article discusses the al-wujuh wa al-nazhair al-Qur'an in a historical perspective. The problem of pronunciation in the Qur'an seems to have emerged since the early generations of Islam. But in its development this study has been hated because it is deemed deviated from the function of the Qur'an which is a guide book (huda) not a book of linguistic practice. This opinion cannot be taken for granted, because understanding the meaning of pronunciation is the first step to understanding the Qur'an. This study explains the history of the development of the science ofal-wujuh wa al-nazhair in the classical and contemporary era. Through qualitative research and the chronic historiographic approach, researchers want to examine how this scientific development is from classical and contemporary times and distorted in each period. The result is that in classical era more work appeared specifically discussing this discourse. While in the contemporary era the discourse ofal-wujuh wa al-nazhair was more applicable and integrated in the commentaries. And more affected by hermeneutic thinking instead.